Markets in West Africa : studies of markets and trade among the Yoruba and Ibo - Hodder, B. W.; Ukwu, U. I. ([Ibadan, Nigeria] : Ibadan University Press, 1969)
Tracing the developments of markets from the simplest periodic markets through to retail shops and large specialized markets in larger towns.
Includes index
Bibliography: p. 251.
II 16/02/2019
Loans
Keywords: Markets